2017
DOI: 10.1002/spe.2522
|View full text |Cite
|
Sign up to set email alerts
|

Industrial experiences from evolving measurement systems into self‐healing systems for improved availability

Abstract: Automated measurement programs are an efficient way of collecting, processing, and visualizing measures in large software development companies. The number of measurements in these programs is usually large, which is caused by a diversity of the needs of the stakeholders. In this paper, we present the application of the self-healing concepts to assure the availability of measurements to the stakeholders without the need for effort-intensive and costly manual interventions of the operators. We study the measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Common research focuses like new languages [11], evaluation and testing [70], [221], modelling [85], learning [50], [219], [249], recovery [23], uncertainty [246], and integration [44] were seen in this phase. A general review of selfimproving system integration can be found in [26] and industrial experience reports in [161], [250].…”
Section: -2020 -The Last Decade -Second Halfmentioning
confidence: 99%
“…Common research focuses like new languages [11], evaluation and testing [70], [221], modelling [85], learning [50], [219], [249], recovery [23], uncertainty [246], and integration [44] were seen in this phase. A general review of selfimproving system integration can be found in [26] and industrial experience reports in [161], [250].…”
Section: -2020 -The Last Decade -Second Halfmentioning
confidence: 99%